Indigenous knowledge and environmental education : a case study of selected schools in Namibia - Sheya, Elieser (Stellenbosch : Stellenbosch University, 2014)
ENGLISH ABSTRACT: In some contemporary discourses, a new dimension of knowledge is increasingly being recognised. Sustainable development is no longer the exclusive domain of western science and technology. There is a growing interest in the role that indigenous people and their communities can play in sustainable development. The integration of indigenous knowledge (IK) into formal school curricula, especially environmental education (EE), is seen as a key approach to making education relevant to rural students. This will also promote the intellectual diversity required to manage the scope, complexity and uncertainty of local and global environmental issues. This study is guided by constructivist approaches and postcolonial perspectives that recognise the differences between IK and western sciences but at the same time concerned with ways in which the two can work together. In particular, this study uses a qualitative case study of selected schools in the Northern part of Namibia to investigate how IK can be used to support EE in rural schools. The National (Namibian) Curriculum for Basic Education and the Life Science curriculum documents have been analysed, focusing specifically on how IK is coupled with EE at school level. The review of the curriculum documents revealed that IK is not only ignored and underutilised in schools, but also systematically undermined as a potential source of knowledge for development. The curriculum continues to reinforce western values at the expense of IK. To gain more insight into existing EE practices in schools and the role that local knowledge can play in school syllabi, six teachers, two advisory teachers and two traditional leaders were carefully selected and interviewed. The basis for this was to possibly challenge and address the needs that learners and their environment have. The participants in this study embraced the inclusion of IK in EE. However, the processes of combining IK with science may be constrained by challenges related to: teachers‟ attitudes, the design of the curriculum, and the way learner-centered education is conceptualised and practiced in schools. The study suggests that, to incorporate IK into EE effectively may require a shift away from the current strong subject-based, content-focused and examination driven EE curriculum. A cross-cultural Science Technology and Society (STS) curricula that includes a broad range of disciplines and provides a context within which all knowledge systems can be equitably compared and contribute to our understanding of the environment is proposed as an alternative curricula framework.